COVID-19 Infection in Spinal Muscular Atrophy Associated with Multisystem Inflammatory Syndrome - Rafat Mosalli; Amirah Al Matrafi; Mohammed A. Ghazi; Gamal A. Aboumousatafa; Bosco Paes (Case Reports in Pediatrics)
The coronavirus disease-2019 (COVID-19) is usually less severe and less prevalent in the pediatric population. Children with preexisting conditions such as neuromuscular impairments and chronic lung disease are more susceptible to COVID-19 and may incur several complications with a poor outcome. We present a case report of a 3-year-old-female with generalized hypotonia and respiratory failure due to spinal muscular atrophy who tested positive for COVID-19 and developed multisystem inflammatory syndrome that was treated with intravenous immunoglobulin and tocilizumab and subsequently died. The report highlights the importance of close surveillance, the use of protective measures during hospital visits, early testing, and diagnosis of COVID-19 in children with neurological disorders.